2017
DOI: 10.1093/jamia/ocx145
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences toward an interactive e-consent application for research using electronic health records

Abstract: This study contributes new insights on how e-consent applications could be designed to ensure that patients' information needs are met when seeking consent for research use of health record information. Also, this study offers a potential electronic approach to meeting the new Common Rule requirement that consent documents contain a "concise and focused" presentation of key information followed by more details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 46 publications
0
72
0
1
Order By: Relevance
“…Quality scores of 2 and 1 were provided to 1 study [ 28 ] and 6 studies [ 29 - 34 ], respectively. The qualitative studies ranged from satisfying 80% or more of the quality criteria (6 studies) [ 35 - 40 ] to satisfying 50% to 60% of the quality criteria (3 studies) [ 41 - 43 ]. Moreover, 3 mixed methods studies met 80% or more of the quality criteria [ 16 , 44 , 45 ], 6 studies met from 57% to 71% of the quality criteria [ 15 , 46 - 50 ], while 1 met only 43% of the quality criteria [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quality scores of 2 and 1 were provided to 1 study [ 28 ] and 6 studies [ 29 - 34 ], respectively. The qualitative studies ranged from satisfying 80% or more of the quality criteria (6 studies) [ 35 - 40 ] to satisfying 50% to 60% of the quality criteria (3 studies) [ 41 - 43 ]. Moreover, 3 mixed methods studies met 80% or more of the quality criteria [ 16 , 44 , 45 ], 6 studies met from 57% to 71% of the quality criteria [ 15 , 46 - 50 ], while 1 met only 43% of the quality criteria [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Research participants advised using a bullet point format with access to additional information if desired [ 28 , 34 , 50 ]. Simple, concise language should be used to encourage a sufficient level of understanding [ 15 , 28 , 40 , 50 ]. The possibility of marking information that participants did not understand was considered useful and was viewed as an opportunity to enhance the discussion with the research staff [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An online questionnaire can test the participants' understanding of the informed consent. In addition to the online information the participants have the opportunity to ask questions and discuss relevant topics with the investigator through a phone or online call before giving the consent [11,12]. Furthermore, a limited number of study sites are involved in VCT.…”
Section: Virtual Clinical Trialsmentioning
confidence: 99%
“…Tablet, mobile, or portal-based systems present new opportunities for effectively providing educational materials necessary for informed patient and research study consent. Qualitative studies assessing user needs and preferences have suggested that these tools might effectively address user concerns and potentially increase participation among under-represented groups [66,67]. However, evaluations have not always found clear wins, with some studies failing to see improvements associated with the use of e-consent [68], and others finding difficulties with complex content [69].…”
Section: Consent Trust and Participant Engagementmentioning
confidence: 99%